GDF15 and Growth Control - Emmerson, Paul J.; Duffin, Kevin L.; Chintharlapalli, Sudhakar; Wu, Xinle (Frontiers in Physiology, 2018)
GDF15 is a distant member of the TGF- superfamily and is widely expressed in multiple mammalian tissues. Its expression is highly regulated and is often induced in response to conditions associated with cellular stress. GDF15 serum levels have a strong association with many diseases, including inflammation, cancer, cardiovascular diseases, and obesity, and potentially serve as reliable predictor of disease progression. A functional role for GDF15 has been suggested in cancer, cardiovascular disease, kidney disease and metabolic disease. However, the knowledge of its pathophysiological function at the molecular level is still limited and requires more investigation. Recent identification of the endogenous receptor for GDF15 may provide additional insight in to its’ molecular mechanisms and relationship to disease states.